Musqueam reference grammar - Suttles, Wayne P., 1918-2005 (First nations languages., 2004)
Here is the long-awaited grammar of the Musqueam dialect of Halkomelem, which Wayne Suttles began work on in the late 1950s. The Musqueam people are the First Nation whose aboriginal territory includes much of the Fraser Delta and the city of Vancouver. Halkomelem, one of the twenty-three languages that belong to the Salish Family, is spoken in three distinct forms: Upriver, by the Suttles of the Fraser Valley; Downriver, of which Musqueam is the only surviving representative; and Island, spoken by the Nanaimo and Cowichan of Vancouver Island. Suttles, an anthropologist, worked with knowledgeable older people, eliciting traditional stories, personal narratives, and ethnographic accounts. The grammar covers the usual topics of phonology, morphology, and syntax, illustrated by numerous sentences selected for their cultural relevance, providing insight into traditional practices, social relations, and sense of humour. There are also chapters on kinship and on space and time as well as five texts and appendices giving an index of grammatical elements, names of places and peoples, and the history of work on Halkomelem. It is written using the terms of traditional grammar as much as possible, without following a particular theoretical perspective. Musqueam Reference Grammar is perhaps the fullest account of any Salish language. It will be welcomed by linguists, anthropologists, and the Musqueam people.